A history of psycholinguistics the pre-Chomskyan era - Levelt, W. J. M. (Willem J. M.), 1938- (Oxford : Oxford University Press, 2013)
How do we manage to speak and understand language? How do children acquire these skills and how does the brain support them? This book provides a personal history of the men and women whose intelligence, brilliant insights, fads, fallacies cooperations, and rivalries created the discipline we call psycholinguistics.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: Psycholinguistics